MODIFICATION OF PUBLIC CONTRACT: BETWEEN RULE OF FAIR COMPETITION AND FREEDOM OF CONTRACT PRINCIPLE - Saputri, Theodora Pritadianing (Faculty of Law, Parahyangan Catholic University, 2018)
It is internationally accepted that public procurement procedure and public contract shall be organized in accordance with the fair competition principle and fulfil the requirement of transparency. Public procurement regulations are necessary to secure the efficient use of taxpayer resources by the government in purchasing goods, services and works from the market and to ensure fair competition among the public contract should be protected and that therefore it would be necessary to amend existing regulations which prohibit or restrict this right derived from freedom of contract. In addition, law makers should also put in place restriction with regard to corporate restructuring which main intention is to circumvent requirements of tender documents.